Long-term prognosis of successful left ventricular substrate modification of electrical storm - Margkarian, Artak; Bogossian, Harilaos; Bandorski, Dirk; Khan, Atisha; Hasan, Fuad; Fortmann, Tobias; Jahaj, Klothilda; Lemke, Bernd; Zarse, Markus (Frontiers in Cardiovascular Medicine, 2022)
ABSTRACT Introduction: The Electrical storm (ES) subsumes a state of electrical instability of the heart, which manifests itself in repeated and potentially fatal ventricular arrhythmias (VA) [ ]. We examine the long-term effects of substrate modification with regards to mortality, ventricular tachycardia (VT) recurrences and hospitalization depending on age, gender, heart function, scare location, VT documentation, postprocedural electrical stimulation (PES) and induced VTs. Methods: From 08/2008 and 09/2019 160 consecutive patients admitted for ES ablation via electroanatomical mapping were followed up until 04/2021. Results: 50/160 patients showed VT recurrences after 13.8±21.7 (0.0-80.3) months, with a characteristic steep curve directly after ES and then a rapid decline leading to a plateau (first month 10/50 (20%), first year 35/50 VT recurrences (70%) Mortality rates followed a similar pattern also the initial decline was not as steep. 42 patients died during the observation period (26%) after 16.6±16.1 (0.0-67.9) months after ablation day (first month (n=7, 16.7%) first year (n=21, 50%). Gender, age, scare localization, missing VT documentation did not worsen outcome. Induction of > 3 VTs and lack of PES due to hemodynamic instability significantly decreased effectiveness. Finding the entry significantly increased long-term effects. Conclusion: Ablation of ED is safe and feasible independent of a variety of factors. Employing more sophisticated tools to understand the reentry mechanism will further improve the long-term outcome.